1997
DOI: 10.1034/j.1399-3054.1997.1010111.x
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin conjugation to endogenous proteins in the dormant tuber of Helianthus tuberosus and during the first cell cycle

Abstract: M. 1997. Ubiquitin conjugation to endogenous proteins in the dormant tuber of Helianthus tuberosus and during the first cell cycle. -Physiol. Plant. 101:77-85.Ubiquitin is a small protein involved in an ATP-dependent proteoiytic pathway in all eukaryotes. This pathway has been demonstrated to be required for both the bulk degradation of cellular proteins and the targeted proteolysis of specific regulatory proteins. We have investigated the presence of ubiquitin (Ub) and the ubiquitin-conjugating system in dorm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…In plants, the ubiquitin-mediated proteolytic pathway is implicated in a variety of cellular processes, including alkaloid synthesis (Fernandez and DeLuca, 1994), senescence and stress responses (Belknap and Garbarino, 1996;Stephenson and Rubinstein, 1998), hypersensitive and defense responses (Becker et al, 1993(Becker et al, , 2000, vascular tissue differentiation (Woffenden et al, 1998), seed formation (Ferreira et al, 1995), and cell cycle regulation (Scoccianti et al, 1997;Genschik et al, 1998).…”
mentioning
confidence: 99%
“…In plants, the ubiquitin-mediated proteolytic pathway is implicated in a variety of cellular processes, including alkaloid synthesis (Fernandez and DeLuca, 1994), senescence and stress responses (Belknap and Garbarino, 1996;Stephenson and Rubinstein, 1998), hypersensitive and defense responses (Becker et al, 1993(Becker et al, , 2000, vascular tissue differentiation (Woffenden et al, 1998), seed formation (Ferreira et al, 1995), and cell cycle regulation (Scoccianti et al, 1997;Genschik et al, 1998).…”
mentioning
confidence: 99%
“…The ubiquitin/26S proteasome pathway controls many important regulatory processes. In plants, the ubiquitin-mediated proteolytic pathway is implicated in senescence and stress responses (Belknap & Garbarino, 1996;Stephenson & Rubinstein, 1998), hypersensitive and defence responses (Becker et al, 1993;2000), vascular tissue differentiation (Woffenden et al, 1998), cell cycle regulation (Scoccianti et al, 1997;Genschik et al, 1998), seed formation (Ferreira et al, 1995), pollen germination (Sperenza et al, 2001) and organogenesis Yanagawa et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In plants, the pattern of ubiquitinated proteins changes during floral development (Courtney et al 1994), zygotic embryogenesis (Almoguera et al 1995), aging and greening of leaves (Veierskov et al 1992), seed formation (Ferreira et al 1995), and cell cycle progression (Scoccianti et al 1997). Callis and Bedinger (1994) observed that a developmentally‐related loss of free ubiquitin and ubiquitinated proteins occurs during pollen maturation in maize inbred line Ky21.…”
Section: Introductionmentioning
confidence: 99%